Pain of Hypertension Patients in Community Setting: Under Working Area of Wanaraja Public Health Centre - Tantri Puspita; Sri Yekti Widadi; Wahyudin Wahyudin; Rudy Alfiyansah; Eldessa Vava Rilla; Eva Daniati; Gin Gin Sugih Permana (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Hypertension is a global issue that has been increasing and impacted individuals and even countries. Pain is a major symptom that is felt by hypertension patients. Pain can be an essential factor that implies secondary prevention requirements. The aim of this study was to explain pain experienced that was detected in hypertension patients that live in a community setting, under the working area of Wanaraja Public Health Center in January 2023. This study used a quantitative descriptive with a cross sectional approach. The number population detected as hypertensive patients was 2. 586. The sampling technique was purposive sampling with 142 participants who joined in this study. The study showed that amount 77% of the respondents were women (109 respondents) and more than 80% was in the middle age and the elderly (41.5%; 41.5%; respectively). The respondents described pain in the categories: severe pain 8%, mild pain 20%, moderate pain 67% and no pain 5%. Most of the respondents were in the stage 2 hypertension category (89% for systolic and 86% for diastolic). A few respondents were in systolic or diastolic hypertension crisis category. (7,7%). Family and community nurses can use VAS as a tool to assess the pain of hypertension patients in Community settings. Keywords: Community Setting, Hypertension, Pain